1999
DOI: 10.1080/001401399185874
|View full text |Cite
|
Sign up to set email alerts
|

Under-reporting of work-related disorders in the workplace: a case study and review of the literature

Abstract: Accurate reporting of work-related conditions is necessary to monitor workplace health and safety, and to identify the interventions that are most needed. Reporting systems may be designed primarily for external agencies (OSHA or workers' compensation) or for the employer's own use. Under-reporting of workplace injuries and illnesses is common due to a variety of causes and influences. Based on previous reports, the authors were especially interested in the role of safety incentive programmes on under-reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
229
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(243 citation statements)
references
References 20 publications
12
229
0
2
Order By: Relevance
“…The adversarial nature of a system is thought to increase in systems that are highly experience rated [Ison, 1998;Pransky et al, 1999;Lippel, 2007;Quinlan et al, 2010]. Although appeals are only a small part of the adversarial process, an increase in appeals over the years can provide an indicator of the increasing adversarial nature of the system.…”
Section: Discourses Underpinning Workers' Compensation Systemsmentioning
confidence: 99%
“…The adversarial nature of a system is thought to increase in systems that are highly experience rated [Ison, 1998;Pransky et al, 1999;Lippel, 2007;Quinlan et al, 2010]. Although appeals are only a small part of the adversarial process, an increase in appeals over the years can provide an indicator of the increasing adversarial nature of the system.…”
Section: Discourses Underpinning Workers' Compensation Systemsmentioning
confidence: 99%
“…Workers are also known to be more likely to report safety problems to their supervisors when they are convinced of the effectiveness of prevention programs (Mullen, 2005). Similarly, it has been shown that when workers perceive little use of the data they report to managers, this becomes a source of low commitment to accident-analysis procedures (Pransky et al, 1999). In their study, Arezes and Miguel (2008) noted that the more positively employees viewed the safety climate (perception of the work environment, personal motivation, and physical demands of the job), the more they reported wearing protective hearing gear.…”
Section: Perceived Risk and Safetymentioning
confidence: 99%
“…Des données québécoises et américaines montrent bien qu'il y a sousdéclaration et sous-indemnisation des problèmes de santé au travail (Gervais 1993 ;Pransky et al 1999 ;Davis, Wellman et Punnett 2001 ;Morse et al 2001), et que les problèmes non indemnisés appartiennent à des couches distinctes de la société, notamment les femmes et les minorités ethniques (Lippel 1999(Lippel , 2000Herbert, Janeway et Schechter 1999). L'excès d'indemnisation des hommes ne représente donc pas nécessairement une différence de danger.…”
Section: Hypothèse Sur L'absence De Dangerunclassified